Optimal pH of zinc protoporphyrin IX formation in porcine muscles: Effects of muscle fiber type and myoglobin content. (March 2019) - Wakamatsu, Jun-ichi; Akter, Mofassara; Honma, Fumika; Hayakawa, Toru; Kumura, Haruto; Nishimura, Takanori
Abstract: This study investigated the effects of pH, muscle fiber type, and precursor levels on zinc protoporphyrin IX (ZnPP) formation in porcine skeletal muscles. ZnPP formation could be classified into three distinct groups with pH optima of 4.75, 5.5, or both. The effects of temperature and incubation time on ZnPP formation at the new optimal pH 4.75 differed significantly from those at pH 5.5 reported in previous studies. Protoporphyrin IX (PPIX) formation at pH 4.75 nearly coincided with that of ZnPP, suggesting that the latter strongly affects the former, as observed at pH 5.5. The amount of ZnPP formed at pH 4.75 was related to the ratio of type I muscle fibers. Although myoglobin degradation occurred at pH 4.75, no decrease in heme content corresponded to the formation of ZnPP and PPIX. These results demonstrate that ZnPP and PPIX are formed by two independent mechanisms in porcine skeletal muscles whose optimal pH values are 5.5 and 4.75. Highlights: ZnPP is formed at two different optimal pH in porcine skeletal muscles. ZnPP formed at pH 4.75 is related to type I muscle fiber ratio. ZnPP and PPIX formation was greater at pH 4.75 than at pH 5.5. Myoglobin degradation was observed during incubation at pH 4.75. At pH 4.75, ZnPP and PPIX were increased without a decrease in heme.